The MicroRNA MiR-29c Alleviates Renal Fibrosis via TPM1-Mediated Suppression of the Wnt/β-Catenin Pathway - Huang, Huiya; Huang, Xiaozhong; Luo, Shengnan; Zhang, Huidi; Hu, Feifei; Chen, Ruyi; Huang, Chaoxing; Su, Zhen (Frontiers in Physiology, 2020)
Purpose: This study aimed to evaluate the mechanism by which miR-29c expression in fibroblasts regulates renal interstitial fibrosis. Methods: We stimulated NRK-49F cells with TGF-β1 to mimic the effects of fibrosis in vitro, while unilateral ureteral obstruction (UUO) was performed to obstruct the mid-ureter in mice. MiR-29c mimic or miR-29c inhibitor was used to mediate genes expressions in vitro. The recombinant adeno associated virus (rAAV) vectors carrying a FSP1 promoter that encodes miR-29c precursor or miR-29c inhibitor was used to mediate genes expressions in vivo, and a flank incision was made to expose the left kidney of each animal. Results: In the present study, TGF-β1 was demonstrated to regulate miR-29c expression through Wnt/β-catenin signaling. In contrast, miR-29c appears to inhibit the Wnt/β-catenin pathway by suppressing TPM1 expression. As suggested by this feedback mechanism, miR-29c may be a key fibrosis-related microRNA expressed by fibroblasts in TGF-β1/Wnt/β-catenin-driven renal fibrosis, and manipulation of miR-29c action may accordingly offer a potential therapeutic pathway for renal fibrosis treatment. Conclusion: MiR-29c expression was downregulated in UUO mouse kidneys as well as TGF-β1-treated NRK-49F cells, which thus inhibits myofibroblast formation via targeting of TPM1. Additionally, the production of extracellular matrix in renal fibroblasts appears to be controlled by the reciprocal regulation of miR-29c action and the Wnt/β-catenin pathway.